eHealth literacy in a migrant community and its association with chronic disease - Garcia, Madalena; Machado, Rosa; Serra, Isaura; João, Ana Lúcia (Frontiers in Public Health, 2025)
IntroductioneHealth literacy or digital health literacy has been widely recognized for its impact on health outcomes. Migrant populations face additional challenges related to low literacy, social vulnerability, and health frailty, which may also indicate reduced levels of digital health literacy. The aim of this study was to assess digital health literacy levels in a migrant population and to examine their relationship with sociodemographic characteristics and health-related variables.MethodsThis descriptive, cross-sectional, and exploratory study used a convenience sample of 101 migrant residents from a neighborhood in the Lisbon Metropolitan Area who were fluent in Portuguese. Non-Portuguese speakers were excluded, which may limit representativeness. The small sample size and the non-probabilistic recruitment strategy also constrain the generalizability of findings. Data collection included a sociodemographic and health questionnaire and the validated Portuguese version of the eHealth Literacy Questionnaire.ResultsParticipants reported generally low levels of eHealth literacy. Statistically significant differences were found between individuals with and without chronic disease: those without chronic disease obtained higher scores in most eHLQ dimensions. Associations were also observed with age and educational level. Effect sizes indicated that these associations ranged from weak (e.g., access to digital services that work, r = 0.286) to moderate (e.g., ability to actively engage with digital services, r = 0.472; digital services that suit individual needs, r = 0.432), providing a clearer picture of the magnitude of effects.DiscussionThe findings show that despite fluency in Portuguese, migrants demonstrated persistent barriers to effectively using digital health tools, particularly those living with chronic conditions. These results highlight the intersection of clinical vulnerability and digital exclusion in this population.ConclusionThis exploratory study, while limited by the exclusion of non-Portuguese speakers, convenience sampling, and a small sample size, contributes valuable evidence on digital health inequalities in migrant communities. Effect sizes indicate that associations between eHL and perceived health status or chronic disease are of small to moderate magnitude, underlining the urgent need for culturally sensitive interventions, targeted training, and policy measures to reduce digital health disparities.